ZAKAH OF AGRICULTURE: FACTORS INFLUENCING FARMERS’ BEHAVIORAL INTENTION TO PAY - Fajriyah, Anisa Nuril; Rahmayati, Anim (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Islam presents zakah in two types: zakah nafs (soul) and zakah maal (wealth). There are many studies for zakah maal; one is zakah of agriculture. Sidoharjo is the district in Sragen that had 9.093 hectares for harvesting area in 2019 and produced 58.802 tons of fresh rice grains in the same year. This study aims to determine the factors that influence the behavioral intention of farmers to pay zakah for agriculture in the district of Sidoharjo. This quantitative research uses 100 respondents who fit the criteria as a sample. Data were collected through the questionnaires distributed directly to farmers, and the analysis method used multiple linear regression analysis. The results showed that subjective norms affect the behavioral intention of farmers to pay zakah for agriculture. Meanwhile, attitudes and understanding have yet to be shown to influence the behavioral intention of farmers to pay zakah for agriculture. This research implies that subjective norms have influenced farmers to pay zakah agriculture. Considering that humans are social beings, this factor can provide a positive signal to increase the application of zakah agriculture for the welfare of others. Future research can perform other variables to find the entire model to increase the power of zakah in the agricultural sector. Educating the farmer and establishing the community to assist the farmer in paying zakah can be the practical implication of this research.